QUESTIONS OF RUSSIAN REGIONS’ TYPOLOGY THROUGH ADMINISTRATIVE FACTOR - A. Nikitin (Вестник университета, 2018)
A question of Russian regions typology development is stated and characterized. The main problems of quantitative, high-quality and quantitative and high-quality approaches to classification of Russian regions taking into account features of the Russian economy development at the present stage are revealed. Methodological approach to a typologization of Russian Federation regions based on factor of eficiency and effectiveness of regional management teams is offered. The purpose, tasks, principles, set of regional management teams’activity eficiency criteria, including economic, social and administrative aspects are formulated.